A COMPARATIVE STUDY ON THE PECTORAL GIRDLE OF GREEN-1NINGED MACAVI/ AND PEAHEN - V. R. Indu; K. M. Lucy; A. R. Sreeranjini; S. Maya; N. Ashok; K.V. Syam (Journal of Veterinary and Animal Sciences, 2012)
A study was conducted on the pectoral girdle of eight year old male green-winged macaw and adult peahen to compare the gross features of the bones and to correlate their morphological peculiarities with its possible functions. The skeleton of the pectoral girdle consisted of clavicle, coracoid and scapula in both the species but presented striking deviations. In peahen, the scapula presented a flat coracoid process, coracoid had a hooklike furcular Tuberosity and furcula was Vshaped with a prominent hypociedium. In green-winged macaw the scapula had a truncated caudal extremity with a convex coracoid process whereas, the coracoid showed a tuberous furcular tuberosity and a well developed scapular process. The furcula was U-shaped with a prominent caudal process, while the hypocledium was absent. All the bones were comparatively stronger in green-winged macaw which could be an adaptation towards the functions necessary to perform the flight stroke.